2021
DOI: 10.1016/j.lfs.2021.119634
|View full text |Cite
|
Sign up to set email alerts
|

Soluble P-selectin as a potential diagnostic and prognostic biomarker for COVID-19 disease: A case-control study

Abstract: Introduction To our knowledge, the diagnostic value of the sP-Selectin level in the diagnosis of COVID-19 disease has not yet been investigated. In this study, we aimed to assess this by evaluating the relationship between sP-Selectin level and the clinical severity of COVID-19 infections. Methods A total of 80 patients (50 with mild to moderate and 30 with severe COVID-19 pneumonia), and 60 non-symptomatic healthy volunteers participated in the study. Following serum i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 39 publications
3
23
1
Order By: Relevance
“…Previous studies have investigated whether laboratory parameters such as monocyte/lymphocyte ratio, CRP, ferritin, lactate dehydrogenase (LDH), interleukin‐6 (IL‐6), D‐dimer, p selectin, calprotectin, and surfactant can be used as biomarkers for the clinical diagnosis and prediction of prognosis for COVID‐19. 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 The sensitivity of the markers for COVID‐19 diagnosis mentioned in these studies ranged between 66% and 97.5%. 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 …”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous studies have investigated whether laboratory parameters such as monocyte/lymphocyte ratio, CRP, ferritin, lactate dehydrogenase (LDH), interleukin‐6 (IL‐6), D‐dimer, p selectin, calprotectin, and surfactant can be used as biomarkers for the clinical diagnosis and prediction of prognosis for COVID‐19. 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 The sensitivity of the markers for COVID‐19 diagnosis mentioned in these studies ranged between 66% and 97.5%. 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 …”
Section: Discussionmentioning
confidence: 94%
“… 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 The sensitivity of the markers for COVID‐19 diagnosis mentioned in these studies ranged between 66% and 97.5%. 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 …”
Section: Discussionmentioning
confidence: 94%
“…Platelets from COVID-19 patients also aggregated more quickly and distributed more widely by fibrinogen and collagen. [ 51 ] Five studies found higher values in COVID-19 ICU patients compared with severe non-ICU COVID-19 patients [ 52 , 53 , 54 , 55 , 56 ]. SARS-CoV-2 interacts with platelets and megakaryocytes via an ACE2-independent mechanism, according to Shen et al [ 52 ], and may influence alternative receptor expression linked with COVID-19 coagulation abnormalities.…”
Section: Resultsmentioning
confidence: 99%
“…COVID-19 + patients had exacerbated and chronic endothelium damage, as evidenced by raised sP-sel. Karsli et al [ 56 ] focused on the diagnostic and predictive relevance of serum soluble sP-Sel levels in COVID-19 illness and found that patients with mild-to-moderate and severe pneumonia had greater serum sP-Sel levels than those with no pneumonia. At the cut-off level of 4.125 ng/ml, sP-Sel levels were reported to be 97.5 percent sensitive and 80 percent specific in the diagnosis of COVID-19.…”
Section: Resultsmentioning
confidence: 99%
“…The expression level of sPselectin is considered a biomarker of inflammation, platelet activation, and vascular and thrombotic diseases. [42][43][44] To reveal the correlation of THCMA's P-selectin inhibition activity with its antithrombosis, anti-inflammation, and antitumor activity, in vivo expression levels of sP-selectin and TNFα were examined. Figure 8A-D show that expression levels of sP-selectin in arterial thrombosis rats, venous thrombosis rats, S180 mice, and ear-edema mice had similar patterns.…”
Section: Downregulation Of Sp-selectin and Tnfα Expression By Thcma In Vivomentioning
confidence: 99%